Student Perceptions of Online-Based Chemistry Learning Implementation during the Covid-19 Pandemic - Citra Ayu Dewi; Afrahamiryano Afrahamiryano; Shorihatul Inayah; Leony Sanga Lamsari Purba; Nurdianti Awaliyah (Postgraduate, University of Mataram, 2023)
This study explains chemistry students' perceptions of online-based chemistry learning during the Covid-19 pandemic. The descriptive quantitative survey method was used for the research. The research was carried out at 16 universities in Indonesia in the Chemistry Education Study Program involving 311 students. A survey technique with a Likert scale was used to collect data. The survey form was created using a Google Forms questionnaire, making it easier for students to access. The data analysis technique utilized in this study was to determine the percentage of data from each questionnaire indication from the disseminated Google form, then interpret it into a data presentation score and analyze each indicator in depth. The results showed that students' perceptions of online-based chemistry learning in chemistry education study programs at 16 universities in Indonesia were in poor criteria, this was obtained from the percentage score on the online enjoy learning indicator by 50%, the content presentation strategy indicator 40%, online media indicators used are 65%, indicators are constrained when online learning is 20%, student readiness indicators are 21% and online learning evaluation indicators are 60%. This research is expected to be a reference for evaluating various parties in online-based chemistry learning, especially regarding students' perceptions of fun learning activities. This study also discusses the problematic tendencies of online-based chemistry learning, namely (1) students' motivation decreases due to boring learning, (2) students' understanding of concepts is reduced because the presentation of learning content is less than optimal, (3) students' readiness to participate in online learning is very lacking because have no previous online learning experience. As a result, the findings of this study can be used as evaluation material in analyzing and developing online learning models during the Covid-19 pandemic.